2017
DOI: 10.1016/j.dnarep.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Template-switching during replication fork repair in bacteria

Abstract: Replication forks frequently are challenged by lesions on the DNA template, replication-impeding DNA secondary structures, tightly bound proteins or nucleotide pool imbalance. Studies in bacteria have suggested that under these circumstances the fork may leave behind single-strand DNA gaps that are subsequently filled by homologous recombination, translesion DNA synthesis or template-switching repair synthesis. This review focuses on the template-switching pathways and how the mechanisms of these processes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 120 publications
2
44
1
Order By: Relevance
“…After by-passing the structural hurdle, replication would continue back on the heavy-strand template. This so-called templateswitching mechanism ( Figure 5B) is well documented in various organisms (Giannattasio et al, 2014;Lovett, 2017), and could take place in mitochondria by the recently reported strand-exchange activity of Twinkle (Sen et al, 2016). Template-switching typically results in the accumulation of catenated circular DNA molecules (Giannattasio et al, 2014), which was in fact observed along with mtDNA deletions in our study on the effects of Twinkle overexpression in fly cells (Ciesielski et al, 2018).…”
Section: What Exactly Happens After the Break?supporting
confidence: 76%
“…After by-passing the structural hurdle, replication would continue back on the heavy-strand template. This so-called templateswitching mechanism ( Figure 5B) is well documented in various organisms (Giannattasio et al, 2014;Lovett, 2017), and could take place in mitochondria by the recently reported strand-exchange activity of Twinkle (Sen et al, 2016). Template-switching typically results in the accumulation of catenated circular DNA molecules (Giannattasio et al, 2014), which was in fact observed along with mtDNA deletions in our study on the effects of Twinkle overexpression in fly cells (Ciesielski et al, 2018).…”
Section: What Exactly Happens After the Break?supporting
confidence: 76%
“…The abundance of IRs in genomes implies a mechanism, acting to maintain perfect IRs in genomes. The mechanism of template switching that was reported in experimental systems to homogenize IR arms during replication is the best known mechanism to explain the enrichment of perfect IRs in genomes ( Lovett 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations arising in imperfect inverted repeats, "quasipalindromes (QPs)" have been noted in a wide range of organisms, from bacteria to humans (reviewed in [16,17]). As has been shown for both yeast and bacteria, these sites constitute hotspots for mutation [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Because DPCs lead to replication stalling [3,4,15], we suspected that certain classes of mutation would also be elevated. Copy-number variation and certain templated-genetic mutations are triggered by misalignments of the nascent strand with a template strand during DNA replication (reviewed in [16,17]). The likelihood of these events is enhanced by difficulties in DNA replication.…”
Section: Introductionmentioning
confidence: 99%